Aplikasi Virtual Tour Sekolah Menengah Pertama (SMP) Negeri 3 Kota Pagar Alam Berbasis Android - Putri Utami; Jemakmun Jemakmun (APTIKOM SUMSEL, 2021)
Technological developments are increasingly rapid, giving rise to many new innovations from technology such as virtual tours. Virtual tour is one of the information media that displays 360? panoramic images in visual form. However, the use of virtual tour applications as a promotional medium and introduction to the school environment is still very little. In this study, the author makes a virtual tour application to help parties from SMP Negeri 3 Kota Pagar Alam in promoting and introducing the virtual school environment. The application development method used in this study is the Multimedia Development Life Cycle (MDLC) which consists of six stages of multimedia development, namely Concept, Design, Material Collecting, Assembly, Tasting, and Destribution. The tools used in this research are Unity 3D, Google Street View Application. The tools used in the development are Use Case Diagrams, and Activity Diagrams. With the formation of this virtual tour application, it can make it easier for all students, teachers and the wider community to see the environment of SMP Negeri 3 Pagar Alam City virtually.